Two Dimensions of Interpersonal Tolerance: Their Prevalence and Etiology in World Civilizations - İnan, Murat (My University, 2019)
This research provides three additional insights into theconcept of tolerance. First, it provides empirical insights tothe previous research, distinguishing between two dimensionsof tolerance; political tolerance and social tolerance. Second,it investigates the extent these two dimensions of toleranceprevail in different civilizations in the world. Third, it showshow etiology of tolerance differs across civilizations. Inshort, this research shows that tolerance of national andreligious groups differs from tolerance of social groups inboth kind and degree and investigates to what extent theprevalence and etiology of these two dimensions of tolerancediffer across civilizations. In this research time seriesevidence from subsequent rounds of the World Values Survey(WVS) for over seventy countries are analysed using OrderedProbit models.

Bu araştırma, hoşgörü kavramına üç yeni bakış açısı sunmaktadır. İlk olarak bu çalışma hoşgörünün siyasi hoşgörü ve sosyal hoşgörü olmak üzere iki boyutunu birbirinden ayrıştıran önceki çalışmalara deneysel bir kavrayış katmaktadır. İkinci olarak dünya medeniyetlerinde bu iki hoşgörü boyutunun yaygınlığını araştırmaktadır. Üçüncü olarak ise hoşgörü nedenbiliminin bu medeniyetler arasında nasıl farklılaştığını göstermektedir. Kısacası, bu araştırma ulusal ve dini gruplara yönelik hoşgörünün sosyal gruplara yönelik hoşgörüden hem tür hem de derece olarak farklı olduğunu göstermekte ve bu iki hoşgörü boyutunun yaygınlığının ve nedenbilimin medeniyetler arasında farklılık gösterdiğini savunmaktadır. Bu araştırmada yetmişin üzerinde ülkeden toplanan Dünya Değerler Anketi'nin sıralı anketlerinden elde edilen zaman serisi verileri Sıralı Probit modelleri kullanılarak analiz edilmiştir.
Kişilerarası Hoşgörünün İki Boyutu: Dünya Medeniyetlerindeki Yaygınlık ve Nedenbilimleri
Keywords: Sosyoloji; Etik; Felsefe